Penerapan Rom (Range Of Motion) Dan Massage Punggung Untuk Mencegah Luka Tekan Pada Lansia Tirah Baring - Nazwa Nur Ashyfa; Dinasti Pudang Binoriang (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Immobilization is an extrinsic variable that can cause problems related to skin integrity. The inability to move freely due to situations that interfere with or limit movement may be directly related to an internal problem such as a chronic illness or health condition. Pressure ulcers or also known as decubitus ulcers, are local injuries caused by pressure or a combination of friction and pressure on the skin and/or underlying tissue, usually over a bony prominence. This research method uses a descriptive case study. The research population consisted of 1 person, namely a patient with heart failure with a nursing diagnosis of Activity Intolerance. The evaluation results from providing back massage (efflurage) and range of motion (ROM) to the client showed a reduction in complaints of soreness while in bed. After being taught range of motion (ROM) the client can do it themselves every time the client wakes up. Apart from that, clients also say they feel fresher after doing efflurage massage. The conclusion from applying ROM to these patients is that there is an increase in the Braden scale score which shows that there is a reduced risk of decubitus or pressure sores in the elderly. Meanwhile, when giving effluerage back massage, results were obtained in the form of client validation which said that the client was fresher, and there was a change in blood pressure results to normal numbers.